Analisis Yuridis Pengaturan Rehabilitasi terhadap Residivis Tindak Pidana Narkotika - Cempaka Arumsari (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
Narcotics abuse is no longer considered a victimless crime, but rather an offense that claims numerous victims and inflicts a prolonged catastrophe upon humanity. Furthermore, an emerging challenge is narcotics cases committed by recidivists, namely individuals who re-offend after having been previously convicted and sentenced. Recidivist status raises juridical issues, as it constitutes grounds for the aggravation of criminal penalties. The objective is to ensure that the imposition of criminal sentences effectively provides a deterrent effect and precludes the offender from repeating the same criminal offense. The existence of narcotics abuser recidivists also creates a distinct dilemma for Law Enforcement Officials. Judges are mandated to impose fair and proportionate sentences in accordance with statutory regulations. The recidivist status of a narcotics abuser frequently serves as a justification for Law Enforcement Officials to bypass the integrated assessment required for rehabilitation. This research utilizes a normative legal research method, employing statutory and conceptual approaches. The legal materials used consist of primary legal materials, taking the form of statutory regulations and court decisions, as well as secondary legal materials, comprising legal books and journals, which are analyzed using a descriptive-analytical method. The research findings indicate that recidivists may obtain rehabilitation even in the absence of an assessment. This research concludes that the objectives of sentencing, in addition to providing a deterrent effect, aim to cure or at least restore the offender's condition through rehabilitation; however, guidelines or jurisprudence are required to ensure legal certainty and consistency of application in the future.